The Impact of Multiple Organizational Climates on Performance of Public Sector Organizations: Evidences form Pakistan - Khan, Noor Ullah; Qureshi, Muhammad Imran; Rasli, Amran MD; Ahmad, Aqeel (International Journal of Economics and Financial Issues, 2015)
The purpose of this study is to examine the relationship among multiple organizational climates and micro level performance (MLP) in public sector organization of Pakistan. The research study has examined that five types of organizational climates (participative, innovative, leadership, service and ethical) effect MLP outcomes. The primary data was collected via standard questionnaire randomly from sample size of 250 employees working at regional head office and various branches of National Database & Registration Authority (NADRA) Peshawar, KPK, Pakistan. In addition standard multiple regressions model was used to test several hypotheses statistically about multiple climate, ‘MLP' outcomes including, group level organizational citizenship behavior (GOCB), exit, and job satisfaction. The research findings have revealed that multiple climates were positively related with MLP outcomes i.e. employees' job satisfaction and GOCB and exit. Keywords: Multiple Climates, Performance, National Database & Registration Authority, Group Level Organizational Citizenship Behavior, Job Satisfaction, Exit, Public Sector Organization JEL Classifications: M00